Choice of Law in International Business Contracts - Ronald Fadly Sopamena (Balobe Law Journal, 2022)
Introduction: Differences in the national legal system and the contract law provisions of each country open up opportunities for conflict and dispute to occur. In addition, differences in national laws that serve as normative references for actors in international trade transactions can also cause doubt and uncertainty for foreign parties. Thus the choice of law can be referred to as the freedom of the parties in a contract to choose which law will be used and applies to the parties in an international agreement considering that the national contract law of each country is very diverse.Purposes of the Research: This writing aims to analyze the choice of law in international business contracts.Methods of the Research: This study uses a normative juridical method. Normative legal research is library research, namely research on secondary data. Secondary data has a scope that includes personal letters, books, to official documents issued by the government.Results of the Research: The legal principles regulated in international business transactions refer to the legal principles of international treaties/contracts agreed upon by the parties, and international trade conventions. The parties involved in international business contracts have the freedom to determine with whom and what the subject matter of the agreement they wish to enter into the contract as long as it does not violate the laws and regulations. Then by entering a choice of law, the parties can easily determine the contents of the business contract because each party can already get clarity about the law that will be used and the interpretation of the contents of the contract so that the implementation of the contract will run more optimally.